Trabalho e pedagogia: considerações a partir dos discursos de pedagogas na escola - Fiorin, Bruna Pereira Alves (2012)
Considering previous research and experience in a graduate in Pedagogy, it was found that the emphasis of the work of pedagogues are at work as a teacher, as described in the public policies, especially Resolution 1 / 2006, which presents teaching as the basis for the Pedagogy Course. Based on this context, I tried to with this research, to understand how pedagogues graduated between 2005 and 2010, in the Pedagogy Course, currently working in schools, understand and describe their work, realizing or not this direction their work to teaching. The theoretical and methodological reference for the development of research presents a dialectical perspective. As a procedure, performed a study, with pedagogues through questionnaires about what they understood and described his work, based on categories: Work, Pedagogy, Pedagogy Course and Pedagogues and, subsequently, held a dialogue group for discussion and problematization of the analysis with the research subjects. The analysis was based on Content Analysis. We conduct also a historical return about Pedagogy course in Brazil, documentary research of the Pedagogic Projects of the Pedagogy Course for 2004 and 2007 and National Curriculum Guidelines for the Pedagogy Course, believing the historicity contributes to a better understanding about the work of pedagogues. Still, in the theoretical reference, there were discussions about work and about the pedagogy as a science of education. This research showed that the Pedagogy still needs to be problematized in order to achieve sustain itself as science of education. Moreover, it is essential that the work of pedagogues be deepened in different contexts in an attempt to demystify the idea that the pedagogue only works in the classroom.